Association of Triglycerides and HbA1c Levels with Stages of Invasive Ductal Breast Cancer: A Prospective Study - Vemuri Helena; Arumugam Suresh; Natrajan Muninathan; Kuppusamy Baskaran; Siddique Ahmed Khan (Journal of Pharmacy and Bioallied Sciences)
Background: This prospective study investigates the association between triglyceride (TG) levels and HbA1c values with different stages of invasive ductal breast cancer (IDC) in female patients. Metabolic alterations, including dyslipidemia and hyperglycemia, are increasingly recognized as potential factors associated with cancer progression. Methods: A total of 150 female patients diagnosed with IDC were included in the study, categorized into four stages of the disease. Triglyceride levels were measured using colorimetry, and HbA1c values were determined using the ion exchange resin method. Descriptive statistics and distributions of TG and HbA1c values were analyzed across the cancer stages. Results: In Stage 1, patients had a mean TG level of 347.5 mg/dL and a mean HbA1c of 10.2%. These values declined in subsequent stages, with Stage 4 patients showing a mean TG level of 208.6 mg/dL and a mean HbA1c of 6.9%. A majority of Stage 1 patients (n = 35) had TG levels between 200 and 499 mg/dL, while Stage 4 had the highest number of patients with TG levels below 150 mg/dL (n = 6). Additionally, a significant proportion of Stage 1 patients had HbA1c values ≥10% (n = 17), indicating poor glycemic control. As the disease progressed, this proportion decreased, with only two patients in Stage 4 having HbA1c levels ≥10%. Conclusion: This study suggests a correlation between lower TG and HbA1c levels and more advanced stages of IDC. These findings highlight the importance of metabolic factors in IDC progression and may inform future research on potential therapeutic targets.